Liver toxicity in the era of immune checkpoint inhibitors: A practical approach. (December 2018) - Belli, Carmen; Zuin, Massimo; Mazzarella, Luca; Trapani, Dario; D'Amico, Paolo; Guerini-Rocco, Elena; Achutti Duso, Bruno; Curigliano, Giuseppe
Highlights: Immunotherapy with immune checkpoint inhibitors represents a standard of care for several solid tumors. Immune-related adverse effects (IRAEs) may potentially hit every organ; perhaps, gastrointestinal, skin and endocrine systems are mostly involved. Liver dysfunction is not a very common IRAEs but when it appears as severe toxicity requires drug discontinuation. Treatment of IRAEs requires the prompt beginning of therapy and in some cases also immunosuppressive agents are needed. Abstract: Immune checkpoint inhibitors have revolutionized the cancer treatment with an approved efficacy in different solid tumors and hematologic malignancies. These agents are increasing the indication in cancer treatment, but can be associated with serious immune-related adverse effects (IRAEs). Dermatologic and gastrointestinal toxicities are the most common IRAE followed by endocrinopathies with a different time of occurrence. Rarely cases of gastrointestinal toxicities are observed almost 2 years after initiation of the therapy. In this review we focus on liver toxicity related to these immunotherapeutic agents for which the largest amount of safety data is available. The management of drug-induced liver toxicity is very complicated and in same cases may take a long period of time to be resolved. A prompt recognition of liver IRAEs and an appropriate management of this event, requiring close collaboration with other specialist figures, could improve its treatment with evident implication on the efficacy of the therapy.